Analysis Of Students' Responses To Face-To-Face Physics Learning Post Covid-19 Pandemic - Anggye Ramadhan; Haris Rosdianto; Andika Kusuma Wijaya (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine students' responses to face-to-face physics learning after previously conducting online learning at Singkawang City High School. The research used a survey method with descriptive data analysis techniques. The population in this study were tenth grade students at State High Schools in Singkawang City. The research sample was taken using cluster sampling technique. The data collection technique used in this study was a questionnaire, namely a questionnaire on responses to post-covid-19 pandemic physics learning with the help of Google Form media. The results showed that students' positive responses to face-to-face learning were higher than negative responses, with positive responses averaging 72% and negative responses only 28%. Based on the categories of Excellent, Good, Fair, and Poor, the highest percentage obtained was in the Excellent category, with 35%.